On the mechanical isotropy and corrosion behavior of tantalum produced via laser beam powder bed fusion - Andrew B. Kustas; Erin Barrick; Jonathan Pegues; Hannah Sims; Mary L. Gucik; Michael Melia; Alexander E. Wilson-Heid; Joshua D. Sugar; Eric D. Hintsala; Kevin M. Schmalbach; Frank W. DelRio; Tyler LeBrun (Additive Manufacturing Letters)
Tantalum (Ta) is a refractory metal with excellent corrosion resistance and biocompatability, high melting temperature and density, and good electrical and thermal conductivity, with applications in capacitors, medical implants and devices, linings in the chemical industry, penetrator projectiles, and nuclear reactors. In this work, we examined the mechanical isotropy and corrosion behavior of tantalum produced through laser beam powder bed fusion (PBF-LB). Electron backscatter diffraction (EBSD), tensile tests, nanoindentation, and environmental and galvanic corrosion tests were utilized to establish structure-property relationships as a function of orientation, temperature, and pH. EBSD showed the horizontal and vertical orientations had different grain size distributions and weak texture. From tensile testing, PBF-LB Ta exhibited comparable strain-at-failure relative to wrought Ta, with significantly higher yield and ultimate strengths relative to ASTM B708. Room-temperature nanoindentation confirmed weak mechanical anisotropy via complementary EBSD images and showed small variations in reduced modulus and hardness after annealing to 800 °C due to oxide formation. The environmental corrosion tests in HCl (acid), NaCl (neutral), and KOH (basic) suggested the corrosion current density for PBF-LB Ta was lower than wrought, signifying slower corrosion for PBF-LB Ta. The passive nature of PBF-LB and wrought Ta was observed during galvanic corrosion; when coupled with titanium, aluminum, or stainless steel, most systems did not show corrosion after 24 hr. In all, the results showed that PBF-LB Ta has comparable or, in some cases, superior mechanical and corrosion properties to wrought Ta.